Government Transformation Programme (GTP): Effects of 4S Approach in Malaysian Government Departments (Journal of Business Management and Accounting, 2015)
The  Government  Transformation  Programme  has  become  the  central  issue  among  the public. For any government to retain its popularity, changes are needed to provide more vibrant,  dynamic,  and  progressive  services  to  its  client,  customer,  and  stakeholders. Therefore,   implementing   McKinsey   approach   is   one   mechanism   to   realise   the transformation  programme.  Implementing  McKinsey  approach  has  long  been  practised by  various  organisations  in  adding  value  to  delivery  and  improving  performance.  This article  demonstrates  findings  of  the  four  out  of  seven  McKinsey  approach  elements implemented  in  two  government  departments  in  Malaysia.  The  survey  method  was conducted  in  this  study  on  respondents  comprising  all  the  stakeholders  dealing  in  the everyday  transactions  with  the  government  departments,  including  suppliers,  vendors, and  many  more.  All  the  questionnaires  were  analysed  and  findings  explained  in  greater detail.  The  four  McKinsey  elements  included  strategy,  structure,  system,  and  shared values  (4S).A  comparison  was  made  between  the  results  of  the  4S  from  both  agencies. Interestingly,  the  results  illustrated  how  the  government  departments  transformed  their operational services by getting the whole organisation to put great efforts to undergo the overall process. The results also indicated that for a government department to undergo transformation, staff’s attitude toward changes, behaviour, and knowledge are crucial in making the process a successful one. Further elaboration on outcomes of each McKinsey elements is discussed in detail. The findings would become a guideline for future research dealing  with  elements  of  McKinsey  approach,  as  well  as  serve  as  a  reference  for  the betterment of any organisation that wants to apply the transformation agenda.